Techno-optimism : progress towards CO2 reduction targets in transport : a UK and London perspective - Banister, D; Hickman, R (Inderscience Publishers, 2009)
Transport is making a very limited contribution to carbon emissions reduction targets in the UK and this paper argues the case for a substantial shift in thinking away from the concentration on technological alternatives to a revised approach that combines technological efficiency with behavioural change. The paper presents a critique of the UK approach to energy and transport, commenting on the limited approach and measures used and their effectiveness. The necessary policy measures are available, but at present there is not sufficient political and public support for wide-ranging, effective action. Technology on its own will not be enough. This message is then reinforced with a more local perspective in London where considerable efforts are being made to make London a sustainable city, but even here where opportunities are present, it is the growth in travel and in particular in aviation, that makes transport-based targets very difficult to achieve.